A MODEL FOR EVALUATING ONLINE GAME PLAYERS: A STUDY OF ENJOYMENT, INTERACTION, FLOW EXPERIENCE, AND MOTIVATION TOWARDS ATTITUDE AND INTENTION BEHAVIOR IN CHINA - Wang, Yongshi; Chaipoopirutana, Sirion (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The purpose of this research is to find out the factors that affect online players. This study’s variables are human-Game Interaction, utilitarian motivation, hedonic motivation, flow experience, perceived enjoyment, attitude, and intention. The researchers observed these variables and put forward four hypotheses to determine the influencing factors. The researchers used China’s "League of Legends" as the research model. 300 respondents select this data through a questionnaire survey on two large-scale communication platforms in China. The first platform is the official forum of "League of Legends" in China, and the second platform is the most used game social software "QQ" in China. ". The researchers used convenience sampling and judgmental sampling to investigate. All data were analyzed using statistical software, and linear regression and multiple linear regression were used to find the most significant factors affecting players’ attitudes and intentions. Use descriptive statistics to provide average and demographic percentages. Besides, the researchers use inferential statistics to test the effects of variables. The results show that human-game interaction has a significant positive correlation with utilitarian motivation and hedonic motivation. Utilitarian motivation, hedonic motivation, flow experience, and perceived enjoyment have a positive impact on the player’s attitude. However, flow experience, perceived enjoyment, and attitude have no influence on the intentions of online player.